CHARACTERIZATION CHARCOAL FROM PALM KERNEL SHELLS BASED CHROMATOGRAPHY GC - MS AND DIFFRACTION X-RD - Nasution, Zainal Abidin; Nasution, Siti Salamah (IJRDO-Journal of Applied Science, 2016)
In 2015, the land area of oil palm plantations in Indonesia has reached 10,701,436 Ha, with details of oil palm plantations owned by the people is 4,810,271 Ha, oil palm plantations belonging to state-owned enterprises is 704,094 Ha and oil palm plantations belonging to private company is 5,207,071 Ha. Based one ton of fresh palm fruit bunches of oil palm will produce 20 % - 23 % of CPO ; 5 % - 7 % PKO and the rest of the solid waste from process that is 20 % - 23 % of oil palm empty fruit bunches; 10 % - 12 % of oil palm fruit fiber and 7 % - 9 % palm kernel shells. Palm kernel shells is are formed from biomass of photo synthetic clorophyl leaves, working as a solar cell that absorbs the energy of sunlight, and the converting carbon dioxide and water into a material containing carbon, hydrogen and oxygen. The material in solid form and if converted can be charcoal of palm kernel shells. Implementation of this study, oil palm shell charcoal is made by roasting treatment of palm kernel shells. Roasting was treated of palm kernel shells obtained average yield was 38.20 % (final roasting temperature of 348 0 C, at the time of palm kernel shells are being roasted no longer smoke). From the analysis of chromatograms GC - MS palm shell charcoal derived organic compounds with dominant composition is Cyclopropyl with a concentration of 14.87 %; Acetic acid with a concentration of 17.01 % ; Benzenesulfonic acid with a concentration of 12.11 % ; Benzene with a concentration of 7.30 % ; Phenol with a concentration of 15.59 %. Determination of oil palm shell charcoal with roasting and from testing XRD results that the quantity of the carbon content of the crystals was 12.28 % and the rest is amorphous carbon content of 87.72%. Amorph carbon is not a solid form that dominates the oil palm shell charcoal. So it becomes a nature as raw material for making oil palm kernel shells charcoal with treatment roasting be the substitution of carbon black.